2013
DOI: 10.1155/2013/598541
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cold-Tolerant Aspergillus spp. to Solubilization of Fe and Al Phosphate in Presence of Different Nutritional Sources

Abstract: Three species of Aspergillus, namely, A. niger, A. glaucus and A. sydowii, isolated from soil samples collected from the Indian Himalayan Region (IHR), have been investigated for solubilization of aluminium phosphate and iron phosphate in the presence of different carbon and nitrogen sources. Preference of each fungal species varied for nitrogen and carbon sources, in terms of phosphate-solubilization. Among three species, Aspergillus niger gave the best results; it solubilized 32% and 8% of the supplemented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Our results of soluble P released by Bacillus grown on a medium containing FePO 4 varied from 34.25 to 52.22 mg L −1 and were lower than the previously reported values for Ca-P solubilization by the same isolates, which ranged from 112 to 179 mg L −1 21 . Similar results, reported previously with different bacterial species, have shown that Fe-P and Al-P are less soluble than Ca-P 31, 32. The highest Fe-P solubilization has been documented in rhizobacteria and fungi4, 32, 33; however, our isolates showed higher solubilization than reported for endophytic bacteria isolated from peanuts, that ranged from 13.9 ± 0.3 to 37.4 ± 2.0 mg L −1 12 .…”
Section: Discussionsupporting
confidence: 74%
“…Our results of soluble P released by Bacillus grown on a medium containing FePO 4 varied from 34.25 to 52.22 mg L −1 and were lower than the previously reported values for Ca-P solubilization by the same isolates, which ranged from 112 to 179 mg L −1 21 . Similar results, reported previously with different bacterial species, have shown that Fe-P and Al-P are less soluble than Ca-P 31, 32. The highest Fe-P solubilization has been documented in rhizobacteria and fungi4, 32, 33; however, our isolates showed higher solubilization than reported for endophytic bacteria isolated from peanuts, that ranged from 13.9 ± 0.3 to 37.4 ± 2.0 mg L −1 12 .…”
Section: Discussionsupporting
confidence: 74%
“…In general, the solubilization of iron phosphate (strengite) in this study was low in comparison with the calcium phosphate (hydroxyapatite). Previous studies have indicated that iron phosphate compounds are less susceptible to microbial solubilization than calcium phosphates (Rinu et al, 2013). pH of the medium during growth are efficient phosphate solubilizers (Nahas, 1996;Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent two decades, several researchers have published the potential utilization of microbial strains from Indian Himalaya. Rhodococcus, Pseudomonas, Bacillus, Serratia, and Ascomycetous fungi (Trichoderma, Aspergillus, Penicillium) have been recognized as promising candidates in agriculture and forestry [100,[109][110][111][112], but they need further attention for obtaining a form of valuable product. Recently, a strain of Stenotrophomonas with multiple plant growth promoting activities and possibilities to utilize as biofertilizer has been reported [113].…”
Section: Bioprospection Of Cold-tolerant Microbes: Versatile and Prommentioning
confidence: 99%